Burnout in Urology: Findings from the 2016 AUA Annual Census. Issue 6 (November 2018) - North, Amanda C.; McKenna, Patrick H.; Fang, Raymond; Sener, Alp; McNeil, Brian Keith; Franc‐Guimond, Julie; Meeks, William D.; Schlossberg, Steven M.; Gonzalez, Christopher; Clemens, Quentin J.
Abstract : Introduction: : Physician burnout is linked to decreased job performance, increased medical errors, interpersonal conflicts and depression. Two recent multispecialty studies showed that urologists had the highest rate of burnout. However, these reports were limited by a low sample size of urologists (119). We aimed to establish the prevalence of urologist burnout and associated factors. Methods: : In the 2016 American Urological Association Census, Maslach Burnout Inventory questions were randomly assigned to half of the respondents. Using matrix sampling, the 1, 126 practicing urologists who received and answered the Maslach Burnout Inventory questions represented the entire 2, 301 who completed the census. Burnout was defined as scoring high on the scales of emotional exhaustion or depersonalization. Demographic and practice variables were assessed to establish factors correlating to burnout. Results: : Overall 38.8% of urologists met the criteria for burnout, with 17.2% scoring high for emotional exhaustion and 37.1% scoring high for depersonalization. Multivariate analysis revealed that urologist burnout is associated with more patient visits per week, younger age, being in a subspecialty area other than pediatric or oncology, in solo or multispecialty practice, practice size greater than 2 and greater number of work hours per week. Conclusions: : These results suggest that the burnout rate for urologists is lower than previously reported, and are consistent with rates reported in other medical and surgical specialties. However, burnout continues to be an important issue. Greater workload correlated with increased burnout while other practice patterns appeared to be protective. It is critical to keep urologists in the workforce to help lessen projected shortages.